2020
DOI: 10.1542/peds.2020-000786
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and Risks of Visitor Restrictions for Hospitalized Children During the COVID Pandemic

Abstract: To control the spread of severe acute respiratory syndrome coronavirus 2, the virus responsible for coronavirus disease 2019, many hospitals have strict visitor restriction policies. These policies often prohibit both parents from visiting at the same time or having grandparents or other family members visit at all. We discuss cases in which such policies created ethical dilemmas and possibly called for compassionate exceptions from the general rules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
91
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(106 citation statements)
references
References 8 publications
2
91
0
13
Order By: Relevance
“…The short-term and long-term effects of these restrictions are unknown, but may be significant. 19 While we found that the majority of parents understood the need for revised visitation policies, they reported significant concerns about their consequent ability to visit, care for, and bond with their infants. The visitation restrictions were implemented between mid-March and early April 2020 in the USA and UK during the early stages of the pandemic.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The short-term and long-term effects of these restrictions are unknown, but may be significant. 19 While we found that the majority of parents understood the need for revised visitation policies, they reported significant concerns about their consequent ability to visit, care for, and bond with their infants. The visitation restrictions were implemented between mid-March and early April 2020 in the USA and UK during the early stages of the pandemic.…”
Section: Discussionmentioning
confidence: 67%
“…Our findings highlight the complex challenges of developing and implementing guidelines during a rapidly evolving novel pandemic, with limited evidence and experience available, and the expected tradeoffs on the established standard of care and its benefits. 19 Some of the impacts may be mitigated by individualising policies to meet the unique requirements of the affected population and local centres, and in situations including end of life care or life-threatening surgeries/procedures, and by constant re-evaluation of emerging evidence and the impact of policies. 19 Policy makers must recognise and reflect that parents are key partners in the care of their baby on the NICU and integral to optimal outcomes.…”
Section: Open Accessmentioning
confidence: 99%
“…Ultimately, as health care systems attempt to prevent the spread of coronavirus, new policies have led to families interacting very differently with their infants in the NICU-or not at all. These rapidly instituted changes may carry with them the risk of secondary unintended consequences [16].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the severe regulations concerning the ban on visits, some special arrangements were available for seriously ill patients in inpatient nursing and especially palliative and hospice care facilities. This exception was at the discretion of the doctor providing the treatment; when exceptional circumstances arise, personalised decisions about visits were reported to be ensured weighing the risks and bene ts arising from visitors [28].…”
Section: Discussionmentioning
confidence: 99%